Analyzing the social networks of high- and low-performing students in online discussion forums - Ghadirian, Hajar; Salehi, Keyvan; Mohd Ayub, Ahmad Fauzi (Routledge, 2018)
An ego network is an individual’s social netwrk relationships with core members. In this study, the ego network parameters in online discussion spaces of high- and low-performing students were compared. The extent to which students’ ego networks changed over the course were also analyzed. Participation in 7 weeks of online discussions were analyzed for 12 high-performing students and 9 low-performing students. Results suggested that ego networks’ compositions of high- and low-performing students were significantly different. Particularly, high-performing students had denser ego networks and tended to exhibit a higher level of centralities than low-performing students. Results of network visualization indicated that high-performing students increased and kept their networks stable over the course in comparison to low-performing students, who had fragmented networks. Several networks’ change mechanisms for high- and low-performing groups are also identified and discussed.